DOES UNIQUENESS OF HUMAN CAPITAL PREDICT INNOVATIVE PERFORMANCE? TESTING THE MODERATING ROLE OF INTRINSIC MOTIVATION IN THE HANDICRAFTS SECTOR OF KASHMIR - Lone, Mushtaq Ahmad; Muneer, Falak; Kakroo, Nisar Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the unique human capital and innovative performance link and the intrinsic motivation as a moderator in this relationship. We obtained exciting results while testing hypotheses by applying Structural Equation Models and the Hayes Approach to the data collected from 196 respondents from the Kashmiri Handicrafts industry. The findings show that innovative performance is enhanced through unique human capital. Moreover, this relationship is significantly moderated by the intrinsic motivation of employees’/ sales persons. Thus, the interactive effect of outstanding human capital and inherent reason can enhance innovative performance by ensuring attractive avenues to enrich unique skills, knowledge, and the like among employees/salespersons. This paper attempted to unveil these relationships that have implications for theory and practice; further, some valuable detections were made under the veil.